AB0784 Effectiveness of anti-tnfs on dactylitis and enthesitis in patients with psoriatic arthritis: results from the corrona psoriatic arthritis/spondyloarthritis registry. (15th June 2017) - Mease, PJ; Singh, R; Douglas, K; Hua, D; Litman, HJ; Karki, C; Griffith, J
Abstract : Background: Dactylitis and enthesitis are common disease manifestations encountered in nearly 10–30% of patients with psoriatic arthritis (PsA). Previous clinical trial data suggests that anti-tumor necrosis factors (aTNFs) are effective in controlling dactylitis and enthesitis among PsA patients, however there are limited data from real world studies. Objectives: To evaluate the effectiveness of aTNFs on dactylitis and enthesitis in patients with PsA enrolled in Corrona, a large US observational cohort of patients with PsA and spondyloarthritis. Methods: Adult PsA patients who initiated or were currently on an aTNF at registry enrollment (baseline) between 3/2013–9/2016 and had a 12 month follow-up visit were included. Dactylitis was defined as a non-zero total dactylitis score on a scale 0–20 and enthesitis was defined by a non-zero score on the SPARCC enthesitis index, 0–16. The primary outcome was change in dactylitis and enthesitis scores at 12 months from baseline. Descriptive analysis of patient characteristics at baseline was examined and change in outcomes was evaluated using t-tests. Results: There were 28 patients with dactylitis and 77 patients with enthesitis who met the inclusion criteria. Patients with dactylitis and enthesitis had a mean (SD): age of 48.2 (14.8) and 53.5 (11.5) years, body mass index of 30.8 (6.6) and 31.4 (7.6), disease duration of 9.3 (9.1) and 8.1 (7.7) years, and 28.6% and 45.5% were on methotrexate combination therapy respectively. Patients had a mean clinical disease activity index of 15.1 in both groups, 40.0% and 17.1% were in minimal disease activity, mean (SD): body surface area was 4.4 (4.4) and 5.2 (9.7), pain was 33.1 (29.5) and 43.3 (27.5) on a visual analogue scale (VAS) of 0–100, and more than 80% and 90% of patients had some morning stiffness in the dactylitis and enthesitis groups, respectively. At 12 months from baseline, there were significant improvements in both dactylitis and enthesitis scores in patients with PsA treated with aTNFs (Table). Conclusions: In this clinical registry, aTNF therapy significantly improved both dactylitis and enthesitis at 12 months. Further evaluation of secondary outcomes and larger studies with comparator cohorts will further validate the effectiveness of aTNFs in improving the outcomes in PsA patients. Acknowledgements: This study is sponsored by Corrona, LLC. The Corrona, LLC has been supported through contracted subscriptions in the last two years by AbbVie, Amgen, BMS, Crescendo, Eli Lilly and Company, Genentech, GSK, Horizon Pharma USA, Janssen, Momenta Pharmaceuticals, Novartis, Pfizer, Roche and UCB. The design, study conduct, and financial support for the study was provided by AbbVie. AbbVie participated in the interpretation of data, review, and approval of the abstract. Disclosure of Interest: P. Mease Grant/research support from: Celgene, Novartis, Abbvie, Amgen, BMS, Janssen, Lilly, Pfizer, UCB, Consultant for: Celgene, Corrona, Merck, Novartis, Abbvie, Amgen, BMS, Crescendo, Genentech, Janssen, Lilly, Merck, Pfizer, UCB, Speakers bureau: Abbvie, Amgen, BMS, Crescendo, Genentech, Janssen, Lilly, Novartis, Pfizer, UCB, R. Singh Shareholder of: AbbVie, Inc, Employee of: AbbVie, Inc, K. Douglas Shareholder of: AbbVie, Inc, Employee of: AbbVie, Inc, D. Hua Employee of: Corrona, LLC, H. Litman Employee of: Corrona, LLC, C. Karki Employee of: Corrona, LLC, J. Griffith Shareholder of: AbbVie, Inc, Employee of: AbbVie, Inc